Carcharhinus limbatus - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Carcharhinus limbatus (Müller & Henle, 1839). Blackfin Shark or Blacktip Shark . To 2.86 m (9.4 ft) TL (Weigmann 2016). Circumglobal in tropical waters; Ensenada, northern Baja California (Ebert 2003) to northern Peru (Chirichigno and Vélez 1998), including Gulf of California (Compagno et al. in Fischer et al. 1995), and Islas Galápagos (Grove and Lavenberg 1997). Unconfirmed records from California (Ebert 2003). Inshore (Compagno 1984); depth: surface to 160 m (328 ft) (min.: Grove and Lavenberg 1997; max.: White and Sommerville 2010). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 18, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008